Numerical Analysis of Masonry-In filled Reinforced Concrete Frames - AL-Shaikh, Ibrahim; Falah, Nabil (University of Science and Technology, Yemen, 2014)
Analytical studies have been conducted to investigate the performance of masonry infill reinforced concrete frames under in-plane lateral loading. In this paper, the experimental results were summarized in concisely, and a constitutive model is presented for the modeling masonry units, mortar, and the masonry units/mortar interface in general. 3D finite element models of reinforced concrete frames have been constructed by ABAQUS software. The concrete damaged plasticity model provided by ABAQUS is used to simulate the behavior of concrete. A comparison was performed between the numerical modeling results and the experimental results, to verify that the finite element models in ABAQUS are capable of simulating similar behavior to experimental models. There is good agreements between experimental and numerical results